Franklin Bowditch Dexter, Biographical Sketches of the Graduates of Yale College: May 1745-May 1763, Annals, at 8 (1745) - (:unkn) unknown (My University, 1745)
Prohibited any scholar from keeping or discharging a gun or pistol in the College.
Keywords: SENSITIVE PLACES